"It's like a reverse Robin Hood—We all know they can't pay": How court actors navigate the logics of monetary sanctions - Shannon, Sarah (Criminology, 2025)
Monetary sanctions (also known as legal financial obligations or LFOs) are the most common form of state sanction for criminal convictions, yet we know little about the logics that court actors use in their implementation. Merging an inhabited institutions perspective with the institutional logics framework, we present evidence from court actors’ accounts of imposing and collecting LFOs to reveal how they navigate the competing penal and fiscal logics of LFO sentencing across eight states. We show that the polyvalent logics underlying LFOs give rise to individual and collective critiques. Amid this discontent, we discern several patterns in how court actors navigate the tensions between coexisting logics and continue their work unabated, including the use of discretion and prioritization of some goals over others. Our analysis demonstrates how court actors make sense of their work within a complex legal field rife with conflicting priorities and how LFO sentencing and collection persist despite the contradictory logics undergirding them. Our theoretical model connecting institutional logics and inhabited institutions frameworks elucidates how decision-making in the criminal legal system operates. Although we specifically examine monetary sanctions, our findings have implications for other contexts in which decision-makers struggle with interpretation, application, and consequence.